2016
DOI: 10.1093/heapol/czw093
|View full text |Cite
|
Sign up to set email alerts
|

Community midwifery initiatives in fragile and conflict-affected countries: a scoping review of approaches from recruitment to retention

Abstract: While community engagement and acceptance were crucial, CMW programmes were weakened by inappropriate recruitment and training, lack of support and general insecurity. Further research and implementation evidence is needed to aid policy-makers, donors and implementing agencies in developing and implementing effective CMW programmes in FCAS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(72 citation statements)
references
References 25 publications
2
70
0
Order By: Relevance
“…Therefore, it is easier for them to communicate with the locals on the health issues that are affecting them. The findings from this study are also similar to the findings from the studies conducted by Rowe et al (2005), Aboshaiqah (2016) and Miyake et al (2016). These three studies found that socio-cultural factors affect the skill level and work ethics of the domestic health care staff.…”
Section: Variations In the Research Findingssupporting
confidence: 88%
See 1 more Smart Citation
“…Therefore, it is easier for them to communicate with the locals on the health issues that are affecting them. The findings from this study are also similar to the findings from the studies conducted by Rowe et al (2005), Aboshaiqah (2016) and Miyake et al (2016). These three studies found that socio-cultural factors affect the skill level and work ethics of the domestic health care staff.…”
Section: Variations In the Research Findingssupporting
confidence: 88%
“…Aboshaiqah (2016) argued that cultural traditions and beliefs in Saudi Arabia affect the skill level of medical staff. Miyake et al (2016) argued that improving the availability of skilled workers during new births is a challenging task in conflicted areas.…”
Section: Theoretical Perspectives Related To Health Care Service Qualmentioning
confidence: 99%
“…The MoH has limited capacity to manage the coordination of the different partners. This limited capacity has been attributed to the shortage of staff to support the directors in their day-to-day activities, including policy formulation, implementation, enforcement, and monitoring [44,51,52].…”
Section: Leadership and Governancementioning
confidence: 99%
“…"You could get anti-leishmaniasis [medication] coming to Western Equatoria where there is no leishmaniasis" [44].…”
Section: Medicines and Suppliesmentioning
confidence: 99%
See 1 more Smart Citation